2016
DOI: 10.1002/pros.23280
|View full text |Cite
|
Sign up to set email alerts
|

Low Intratumoral Mast Cells Are Associated With a Higher Risk of Prostate Cancer Recurrence

Abstract: Our results suggest that intratumoral mast cells may be protective against prostate cancer recurrence and could potentially serve as a prognostic biomarker after prostatectomy. Prostate 77: 412-424, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
3
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 40 publications
5
54
3
4
Order By: Relevance
“…In tissue samples from specimens containing prostate cancer, there are increased mast cell numbers in areas of prostate cancer versus benign prostate tissues, and mast cells numbers are higher in density in lower Gleason grade than in higher Gleason grade cancers [14,[19][20][21][22][23]. We and others have reported that high intra-tumoral mast cell numbers are associated with favorable prognosis [14,19,23]. The opposite association exists for extra-tumoral mast cells, where high mast cell numbers are associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In tissue samples from specimens containing prostate cancer, there are increased mast cell numbers in areas of prostate cancer versus benign prostate tissues, and mast cells numbers are higher in density in lower Gleason grade than in higher Gleason grade cancers [14,[19][20][21][22][23]. We and others have reported that high intra-tumoral mast cell numbers are associated with favorable prognosis [14,19,23]. The opposite association exists for extra-tumoral mast cells, where high mast cell numbers are associated with worse prognosis.…”
Section: Introductionmentioning
confidence: 75%
“…The opposite association exists for extra-tumoral mast cells, where high mast cell numbers are associated with worse prognosis. We previously analyzed mast cell density in relation to race and both biochemical recurrence (PSA progression) and the development of metastases after radical prostatectomy [14,24]. Our findings highlight an important predictive role for high numbers of benign tissue (extra-tumoral) mast cell numbers in association with a higher risk of both biochemical recurrence and metastases in both African-American and European-American men [14,24].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Hempel et al (66) showed a protective role of intratumoral mastocytes connecting a low number of intratumoral mast cells with a higher risk of prostate cancer recurrence (66). …”
Section: Prostate Cancer and Inflammationmentioning
confidence: 99%